Blood pressure control among hypertensive patients with and without diabetes mellitus in six public primary health care clinics in Malaysia - Cheong, Ai Theng; Tong, Seng Fah; Shariff Ghazali, Sazlina; Abdul Samad, Azah; Md Sharif, Salmiah (Sage Publications, 2015)
Hypertension is a common comorbidity among diabetic patients. This study aimed to determine blood pressure (BP) control among hypertensive patients with and without diabetes. This was a cross-sectional study in 6 public primary care clinics in Wilayah Persekutuan, Malaysia. Hypertensive patients aged ≥18 years and attending the clinics were selected via systematic random sampling. The BP control target was defined as <130/80 mm Hg for diabetic patients and <140/90 mm Hg for nondiabetic patients. A total of 1107 hypertensive patients participated in this study and 540 (48.7%) had diabetes. About one fourth (24.3%) of the hypertensive patients with diabetes achieved BP control target, compared with 60.1% patients without diabetes (P < .001). Being diabetic and on ≥2 antihypertensive treatments were associated with poor BP control. Attention needs to be given to these groups of patients when managing patients with hypertension.